AL-QUR’AN, HADITS, DAN IJTIHAD SEBAGAI PEDOMAN HIDUP UMAT ISLAM - Syahriani Syahriani; Meliati Meliati; Zukhrufi Nahla; Muhammad Rifai Harahap (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to analyze the sources of Islamic teachings as a guide for the life of Muslims. The primary sources used are the Qur’an and Hadith, with ijtihad serving as an additional source to understand issues not explicitly explained. The research employs a qualitative descriptive approach through literature review, collecting data from books, scientific journals, as well as studies of Qur’anic verses and their translations. The results indicate that understanding and practicing Islamic teachings must be based on authentic sources, so that Islamic values can be correctly applied in daily life. This study provides a comprehensive overview of the role of the Qur’an, Hadith, and ijtihad in shaping the laws and guiding principles of Muslim life.